DIVERGENT SCHEMES FOR BACKLEY-LEVERETT PROBLEM APPLICATION - Yu. P. Krupnov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The set of difference schemes for the one-dimentional Backley-Leverett problem is considered.